Barriers to Academic Entrepreneurship in Lower Silesia. Research Results - Wachowska, Małgorzata (Regional Barometer. Analyses & Prognoses, 2016)
The subject of this paper is a form of academic entrepreneurship that manifests itself in sales of academic inventions in the form of either patents or licenses. The aim of this paper is to indicate reasons for which academic researchers from Lower Silesia (Poland’s NUTS 2 region) do not engage in the commercialization process of inventions they create. On the basis of information obtained during direct interviews with academic researchers from Lower Silesia it may be concluded that the main barrier to academic entrepreneurship in Lower Silesia is the use of inadequate policy instruments that encourage academic researchers only to generate inventions and submit them for patent protection but little motivate them to engage in research commercialization.